AFFIRMATION OF SERBIAN SCULPTURES IN KOSOVO AND METOHIJA (Heritage, 2022)
The paper discusses the affirmation of Serbian sculptors in Kosovo and Metohija in the second half of the XX century. It began to develop in the province in parallel with painting, and the founding of the Academy of Arts in Pristina in 1973 can be taken as a turning point. Most artists have already been involved in current creative trends in fine arts in Kosovo and Metohija and beyond. Bužančić says that sculptural achievements, as well as facts from the art scene at the time and a promising future, reject any allusion that sculpture was still a less important sector of Kosovo's art. As the founders of Serbian sculpture in Kosovo and Metohija, we can mention Svetomir Arsić Basara, Radoslav Musa Miketić, and after some time Zoran Karalejić, and they raised sculpture in Kosovo and Metohija with their artistic creation and pedagogical work. The circle of Serbian sculptors then began to expand and prosper, with new profiles and sensibilities, enriching sculptural production in the province.
Keywords: sculpture, Kosovo and Metohija, Svetomir Arsić Basara, Radoslav Musa Miketić, Zoran Karalejić